Modulation, Plasticity and Pathophysiology of the Parallel Fiber-Purkinje Cell Synapse - Hoxha, Eriola; Tempia, Filippo; Lippiello, Pellegrino; Miniaci, Maria Concetta (Frontiers in Synaptic Neuroscience, 2016)
The parallel fiber-Purkinje cell synapse represents the point of maximal signal divergence in the cerebellar cortex with an estimated number of about 60 billion synaptic contacts in the rat and 100,000 billions in humans. At the same time, the Purkinje cell dendritic tree is a site of remarkable convergence of more than 100,000 parallel fiber synapses. Parallel fibers activity generates fast postsynaptic currents via AMPA receptors, and slower signals, mediated by mGlu1 receptors, resulting in Purkinje cell depolarization accompanied by sharp calcium elevation within dendritic regions. Long-term depression and long-term potentiation have been widely described for the parallel fiber-Purkinje cell synapse and have been proposed as mechanisms for motor learning. The mechanisms of induction for LTP and LTD involve different signaling mechanisms within the presynaptic terminal and/or at the postsynaptic site, promoting enduring modification in the neurotransmitter release and change in responsiveness to the neurotransmitter. The parallel fiber-Purkinje cell synapse is finely modulated by several neurotransmitters, including serotonin, noradrenaline, and acetylcholine. The ability of these neuromodulators to gate LTP and LTD at the parallel fiber-Purkinje cell synapse could, at least in part, explain their effect on cerebellar-dependent learning and memory paradigms. Overall, these findings have important implications for understanding the cerebellar involvement in a series of pathological conditions, ranging from ataxia to autism. For example, parallel fiber-Purkinje cell synapse dysfunctions have been identified in several murine models of spinocerebellar ataxia (SCA) types 1, 3, 5 and 27. In some cases, the defect is specific for the AMPA receptor signaling (SCA27), while in others the mGlu1 pathway is affected (SCA1, 3, 5). Interestingly, the parallel fiber-Purkinje cell synapse has been shown to be hyper-functional in a mutant mouse model of autism spectrum disorder, with a selective deletion of Pten in Purkinje cells. However, the full range of methodological approaches, that allowed the discovery of the physiological principles of PF-PC synapse function, has not yet been completely exploited to investigate the pathophysiological mechanisms of diseases involving the cerebellum. We, therefore, propose to extend the spectrum of experimental investigations to tackle this problem.